Fast axonal transport of the proteasome complex depends on membrane interaction and molecular motor function - Otero, Maria Gabriela (2014)
Protein degradation by the ubiquitin-proteasome system in neurons depends on the correct delivery of the proteasome complex. In neurodegenerative diseases, aggregation and accumulation of proteins in axons link transport defects with degradation impairments; however, the transport properties of proteasomes remain unknown. Here, using in vivo experiments, we reveal the fast anterograde transport of assembled and functional 26S proteasome complexes. A high-resolution tracking system to follow fluorescent proteasomes revealed three types of motion: actively driven proteasome axonal transport, diffusive behavior in a viscoelastic axonema and proteasome-confined motion. We show that active proteasome transport depends on motor function because knockdown of the KIF5B motor subunit resulted in impairment of the anterograde proteasome flux and the density of segmental velocities. Finally, we reveal that neuronal proteasomes interact with intracellular membranes and identify the coordinated transport of fluorescent proteasomes with synaptic precursor vesicles, Golgi-derived vesicles, lysosomes and mitochondria. Taken together, our results reveal fast axonal transport as a new mechanism of proteasome delivery that depends on membrane cargo ‘hitch-hiking’ and the function of molecular motors. We further hypothesize that defects in proteasome transport could promote abnormal protein clearance in neurodegenerative diseases.